Evolution of an audit and monitoring tool into an infection prevention and control process. Issue 1 (September 2016) - Denton, A.; Topping, A.; Humphreys, P.
Summary: Background: In 2010, an infection prevention and control team in an acute hospital trust integrated an audit and monitoring tool (AMT) into the management regime for patients with Clostridium difficile infection (CDI). Aim: To examine the mechanisms through which the implementation of an AMT influenced the care and management of patients with CDI. Methods: A constructivist grounded theory approach was used, employing semi-structured interviews with ward staff ( N = 8), infection prevention and control practitioners (IPCPs) ( N = 7) and matrons ( N = 8), and subsequently a theoretical sample of senior managers ( N = 4). All interviews were transcribed verbatim and analysed using a constant comparison approach until explanatory categories emerged. Findings: The AMT evolved into a daily review process (DRP) that became an essential aspect of the management of all patients with CDI. Participants recognized that the DRP had positively influenced the care received by patients with CDI. Two main explanatory themes emerged to offer a framework for understanding the influence of the DRP on care management: education and learning, and the development and maintenance of relationships. Conclusion: The use of auditing and monitoring tools as part of a daily review process may enable ward staff, matrons, and IPCPs to improve patient outcomes and achieve the required levels of environmental hygiene if they act as a focal point for interaction, education, and collaboration. The findings offer insights into the behavioural changes and improved patient outcomes that ensue from the implementation of a DRP.